Vertical Shaft Kinetic Turbine Performance Using A Cup-Shape Blade - Lempoy, Kennie Abraham; Monintja, Nita C.V.; Lakat, Arwanto M.A. (Universitas Negeri Malang, 2023)
The abundant availability of alternative energy sources forms the fundamental foundation for rural energy development. In particular, renewable energy sources are indispensable in rural areas due to their eco-friendly nature and widespread accessibility, which helps preserve the environment by avoiding pollution. Indonesia, a country blessed with vast water resources, especially its rivers, holds enormous potential for harnessing kinetic energy derived from fast-flowing river waters. Effective utilization of this kinetic energy has the potential to address energy shortages in the country. In this context, there is a pressing need to enhance the efficiency of kinetic turbines designed to function as electricity generators in rural regions. This study focuses on evaluating the impact of variables such as the guide angle, water flow speed, and turbine rotation on turbine power and efficiency. The study employs an experimental approach to achieve its objectives, involving tests to assess the performance of a vertical shaft kinetic turbine equipped with bowl blades. Data analysis based on the experimental findings enables the determination of both turbine power and efficiency. The study outcomes demonstrate that the bowl blade type turbine outperforms the curved blade type, primarily due to its larger water capacity, which significantly exceeds that of the curved blade variant. This study emphasizes the potential for harnessing kinetic energy efficiently in rural areas to support sustainable energy development.